Implementasi SIG dalam Menentukan Potensi Kerawanan Tanah Longsor sebagai Evaluasi Rencana Tata Ruang Wilayah - Ahmad Amri Nur; Dian Sandri; Naufal Haidar Ahmada; Revi Aulia Purbandini (STMIK Budi Darma, 2024)
The problem of natural disasters in the form of landslides is the most common disaster event in Purbalingga Regency. In fact, landslides occur in almost all regions with increasing frequency. There is a need for potential vulnerability to landslide hazards so that landslide disaster mitigation can be carried out, especially in residential areas. Landslide susceptibility mapping is also an evaluation tool for Regional Spatial Planning (RTRW) material, especially spatial pattern plans. This research aims to determine and map the potential for landslide vulnerability in Purbalingga Regency using a geographic information system (GIS) and evaluate the spatial pattern of the RTRW of Purbalingga Regency. The method used to determine landslide susceptibility is weighting and scoring parameters. The research results show that areas with low class landslide vulnerability are 7,391 Ha (9%), medium class are 33,992 Ha (42%), high class are 30,685 Ha (38%) and very high class are 8,296 Ha (11%). A total of 9 sub-districts have very high potential for landslides. The results of overlay calculations of landslide susceptibility maps and spatial patterns found that 6,658 ha of protected areas were in high landslide susceptibility zones and 4,652 ha were in very high landslide susceptibility zones. The 24,203 ha cultivation area is in the high landslide vulnerability zone and 3,643 ha is above the very high landslide vulnerability zone. So these findings can be taken into consideration in revising the RTRW for mitigating landslide hazards, especially for residential areas